Investigating The Tourism Potential Of Nagari Pasilihan: Uncovering A Hidden Paradise In Ranah Minang - Rikarno, Riki; Fadilla, Siti; Marhen, Marhen; Safitra, Kurniawan; Anggara, Angga (LPPM Institut Seni Indonesia Padangpanjang, 2023)
his article aims to prove that Nagari Pasilihan in Solok Regency has extraordinary natural and cultural resources, where these natural riches create a variety of beautiful tourism potentials. Data were obtained directly through observation and documentation. Other sources for this research also include the internet. The collected data were then adjusted between internet data and on-site conditions, along with interview results to ensure the validity of the presented data.Findings in this article include several attractive tourism potentials to be promoted, such as cultural activities within the community involving customs and traditions, a sacred grave of a respected figure believed to vibrate during significant events in the region, the beautiful Ombilin River with its clear water suitable for rafting, valuable and fascinating green stones, the Lubuk Larangan fish as part of the yearly cultural harvest, the panoramic view of Bukik Palano showcasing the beauty of the surrounding area from the summit, and the pine forest that can be a family tourist destination.Based on these findings, there is a wealth of natural potential that can be developed into tourist attractions for the wider community, and Nagari Pasilihan Solok can be considered a